The understanding of curriculum philosophy among trainee teachers in regards to soft skills embedment - Hassan, Aminuddin; Maharoff, Marina (Canadian Center of Science and Education, 2014)
Curriculum philosophy may assist in learning practices that coincide with the philosophy of educational institution and community. This study was aimed to understand how the teacher trainees who pursued Bachelor of Teaching (PISMP) understand the embedment of soft skills into learning activities for core courses in Malaysian Institutes of Teacher Education (IPGMs). This is necessary because embedding soft skills is sometimes considered to be out of interest among the teacher trainees that may lead to neglect the aspects of soft skills development among them. The study was conducted using a case study methodology through the qualitative approach. The respondents comprised of nine teacher trainees from the final year of study. The results yielded the teacher trainees’ beliefs and identified the ways soft skills were embedded among them as they pursued their course. The results of this study allowed those involved in the development of teacher trainees’ soft skills to generate ideas to develop a model to embed soft skills, in line with the interpretation of soft skills, for the teacher trainees in the IPGM.